The Efforts of the Sabhara Unit in Preventing the Circulation of Alcohol in Bandung Police Jurisdictions - Ni Komang Ayu Candrawati (Advances in Police Science Research Journal, 2021)
This research was motivated by the high circulation of alcohol in the Bandung District Police, especially the Majalaya and Baleendah Polsek despite the issuance of Bandung Regency Regional Regulation No. 9/2010 concerning the Prohibition of the Circulation and Use of Alcoholic Drinks. Drinking alcohol is one of the triggers for other crimes. Therefore, a study was conducted that aimed to describe the circulation of alcohol in the jurisdiction of the Bandung Police, the efforts of the Sabhara Unit to prevent problems with the circulation of alcohol in the jurisdiction of the Bandung Police and the factors that influence it. This study uses several theories and concepts, namely the Concept of Effort, the Concept of the Sabhara Unit, the Concept of Prevention, the Concept of Liquor, the Theory of Crime Prevention, The Theory of Management and The Theory of the Legal System. The research was conducted with a qualitative approach, using analytical descriptive research methods, as well as data collection techniques by interviewing, observing and reviewing documents. The results of the study found that: the circulation of alcohol in the jurisdiction of the Bandung Police is still widely carried out in private by traders, especially in the areas of the Baleendah and Majalaya Polsek, the efforts that have been made by the Sabhara Unit in preventing the circulation of alcohol in the jurisdiction of the Bandung Police, both at the Baleendah Police and in the Majalaya Police, namely by carrying out limited tipiring action. However, in its implementation, it is still not optimal, there are supporting factors, namely facilities and infrastructure, factors supporting other functions, factors of public attention and support, the existence of Perda No. 9/2010 concerning the Prohibition of the Circulation and Use of Alcoholic Drinks, while the inhibiting factors are structural factors. organization, human resource factors, budgetary factors, cross-agency cooperation factors and organizational policy factors. Based on the results of the research, the authors suggest that the Bandung Police Chief propose additional personnel and improve cross-agency cooperation. Apart from that, there was an increase in the implementation of tipiring action. As well as for the Kasat and Kanit Sabhara to carry out alcohol raids in accordance with the applicable rules and procedures.